2018
DOI: 10.1016/j.acvd.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of very low frequency at spectral analysis among patients with unexplained syncope assessed by head-up tilt testing

Abstract: VLF at rest predicted the incidence of syncope during HUTt. Further studies are warranted to confirm these preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…According to them, a slight rise of HR (≤18 bpm) in the first 6 min indicates a negative HUT test result. Ciliberti et al (2018) compared HUT(+) patients with HUT(–). They found that very low frequency spectra component of heart rate during rest could be an independent predictor of syncope.…”
Section: Discussionmentioning
confidence: 99%
“…According to them, a slight rise of HR (≤18 bpm) in the first 6 min indicates a negative HUT test result. Ciliberti et al (2018) compared HUT(+) patients with HUT(–). They found that very low frequency spectra component of heart rate during rest could be an independent predictor of syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability (HRV) is an effective indicator of the activities of the autonomic nervous system (i.e., the balance between sympathetic and vagal activity) and is widely used to assess the autonomic response to various internal and external factors ( Acharya et al, 2006 ; von Borell et al, 2007 ; Billman, 2011 ). Indeed, the responses to a variety of physiological, psychological, and clinical factors such as exercise effects ( Pradhapan et al, 2014 ; Valenzano et al, 2016 ), anxiety ( Chalmers et al, 2014 ; Cotoia et al, 2018 ), and health conditions (e.g., cardiac diseases, Watanabe et al, 2017 ; Ciliberti et al, 2018 ; Sessa et al, 2018 ; viral infection, Carter et al, 2014 ; and obesity, Mehta, 2015 ; Messina et al, 2017 ; Triggiani et al, 2017 ) have been intensively investigated using HRV analysis in recent human studies. However, HRV is simultaneously affected by several interdependent physiological and environmental factors ( Fatisson et al, 2016 ) because the sinus node acts as the final summing element of stimuli from the sympathetic and vagal nerves, and their relationship is reflected in the actual heart inter-beat intervals ( Voss et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, further statistical differences in these indicators were not observed in different hemodynamic types of VVS. Ciliberti et al (19) observed that there was a significant statistical difference in VLF between the syncope and non-syncope groups in adults in the supine position (2421.09 ms 2 vs. 895.49 ms 2 , P < 0.01). According to the receiver operating characteristic (ROC) curve (AUC = 0.889), VLF > 2,048 ms 2 was recommended as the best cutoff value for predicting syncope during HUTT, and its sensitivity, specificity, positive predictive value, and negative predictive value were 87.5%, 72.2%, 75%, and 89%, respectively.…”
Section: Head-up Tilt Test and Heart Rate Variabilitymentioning
confidence: 95%